Effect of seed treatment and foliar spray with fungicides in controlling black point disease of wheat (Bangladesh Journal of Agricultural Research, 2009)
The efficacy of seed treatment and foliar spray with fungicides in controlling black point incidence of wheat seeds was evaluated in the field. Two seed treating fungicides, namely Vitavax-200 and Homai-80WP were used @ 0.25% of dry seed weight and foliar spray with Tilt-250EC (0.05%) was applied in six different schedules. Untreated and unsprayed controls were also maintained. Seed treatment with either Vitavax-200 or Homai-80WP significantly increased plant population and grain yield, but none of them was found effective in reducing black point incidence. On the other hand, foliar sprays with Tilt-250EC under all the spray schedules except spraying at 70 and 90 DAS significantly minimized the disease severity over unsprayed control. Among the different spray schedules, spraying at 30, 40, 50, 60, 70, 80, and 90 DAS appeared to be most effective, which was similar to spraying at 30, 45, 60, 75, and 90 DAS in reducing black point incidence and increasing grain yield. Economic analysis on yield advantage showed that the highest additional gross margin of Tk. 6120/ha with BCR 2.57 was obtained from five sprays applied at 30, 45, 60, 75, and 90 DAS. Key Words: Seed treatment, foliar spray, black point, wheat. DOI: 10.3329/bjar.v34i3.3968 Bangladesh J. Agril. Res. 34(3) : 425-434, September 2009